Impact of early and late morning supervised blood flow restriction training on body composition and skeletal muscle performance in older inactive adults - Peskett Logan E.; Thomson Amy M.; Arnason Julia K.; Paudel Yadab; Sénéchal Martin (Translational Exercise Biomedicine, 2025)
To investigate the impact of a supervised blood-flow restriction (BFR) training program performed at different times of the morning on body composition and muscle performance in older, inactive adults.